REMEDIAL TEACHING PROGRAM FOR LOW-ACHIEVERS: AN EFL TEACHER’S PERCEPTION - Noprianto, Eko - (ETERNAL (English, Teaching, Learning, and Research Journal), 2019)
In schools like in Indonesia in which the majority of the classrooms are dominated by students coming from various cultures, different personality, different learning strategies, different background knowledge, and different pace in learning as well, it is certainly difficult for the teachers to accommodate all students’ needs which then results to have students who cannot reach the learning objectives. Thus, remedial teaching program is demanded to address those failing students. However, the debate on whether or not remedial teaching was effective for low-achievers continued among scholars. Besides, the attention on remedial teaching program in Indonesian context was also limited. This case study involving one EFL teacher of a Junior High School in Riau was conducted to explore her perception on remedial teaching program and to find out what problems she encountered in conducting it. Using an interview supported with documents analysis, the researcher found that although the teachers admitted that low-achievers benefited from remedial teaching program, it was difficult for the teacher to design and conduct effective remedial teaching program mainly due to time limitation. Besides, the difficulty in simplifying teaching materials, students’ learning overload and lack of school support were seen to be other problems encountered by her in conducting the program.